ENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN PERILAKU WORD OF MOUTH MAHASISWA PENDIDIKAN OLAH RAGA DAN KESEHATAN DI UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA - LAKSONO SUMARTO (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2014)
The purpose of this study was (1) to analyze the impact of service quality to the satisfaction of students on Sport and Health Education Department at Tunas Pembangunan University (2) to analyze the impact of service quality to the Behaviour Word of Mouth students on Sports and Health Education Department at Tunas Pembangunan University. (3) to measure satisfaction in mediating the impact of service quality to Word of Mouth Behaviour students of Education Department on Sports and Health Education at Tunas Pembangunan University. (4) to determine the most dominant factors of service quality to Word of Mouth Behaviour students of Education Department on Sports and Health Education at Tunas Pembangunan University. Research conducted at Tunas Pembangunan University Surakarta. The population of this research are the students of education Department Sport and Health Tunas Pembangunan University of fourth semester (2nd year) they are 400 Students. From them we took 80 students to be respondents by proportional random sampling. Methods of data collection uses questionnaires and data analysis techniques uses regression analysis path , t Test , and F test. Regression analysis found that there are significant service quality on satisfaction and Word of Mouth Behaviour Student of Education Department on Sport and Health at Tunas Pembangunan University. Satisfaction mediates the effect of service quality Department on Sport and Health Tunas Pembangunan University. Responsiveness factor is the most dominant influence on Student Word of Mouth. Student satisfaction variables mediate the impact of service quality on WOM behaviour of a student with a coefficient mediation of 0.0312. This means that if the respondent's perception of service quality is enhanced through student satisfaction will increase WOM perilau students, while the influence of the quality of student services to students directly WOM behaviour of 0,702. Assuming other factors constant. It can be concluded that the students' satisfaction positively mediates the effect of service quality on WOM behaviour of students.